Relationships between negative life events and suicidal ideation among youth in China: The direct and moderating effects of offline and online social support from gender perspective - Xin, Moye; Petrovic, Julia; Zhang, Lijin; Yang, Xueyan (Frontiers in Psychology, 2022)
Background: Suicidal ideation was proved to be a critical precondition leading to the occurrence of subsequent suicidal behavior. Studies have confirmed that negative life events and forms of social support that youth are experiencing in the current socio-cultural context might have unique impacts on their suicidal ideation. However, the specific mechanism is relatively underexplored. Objective: We sought to investigate the impacts of offline and online social supports on Chinese students’ suicidal ideation under the pressure of various negative life events, as well as potential gender differences in these relationships. Methods: Participants were 2,018 middle - high school and university students from Northwestern China, who completed a demographics questionnaire and self-report measures of negative life events, social support, and suicidal ideation. Results: Offline social support had a significant direct effect on suicidal ideation across genders. Among male youth, offline social support only had a moderating effect on the relationship between punitive negative life events and suicidal ideation. Among female youth, offline social support had a significant moderating effect on suicidal ideation under the pressure of all types of negative life events; Online social support only had a significant direct effect on female youth's suicidal ideation, although it did significantly moderate the relationship between all types of negative life events and suicidal ideation, across genders. Conclusions: Our findings revealed direct and moderating effects of offline and online social support on suicidal ideation among youth under the pressure of different types of negative life events, as well as gender-specific patterns in these relationships.